Effect of soil C:N:P stoichiometry on plant-microbe-soil interactions - Cárdenas Hernández, Julián Fernando (Jihočeská univerzita, 2022)
The effect of C:N:P stoichiometry on plant-microbe-soil interactions was studied using glasshouse experiments to maintain constant environmental conditions and manipulate plant and soil characteristics. Plants with different economic strategies were studied on soils with different C:N:P stoichiometry due to C enrichment. This allowed for various plant-soil interactions, which were used to study the strongest links between plants, microbes, and soil. Subsequently, the role of C addition in the plant-exudates-microbe-soil interactions was evaluated, including the correlation of foliar isotopic C and N composition with plant biomass and soil N availability. Finally, plant- soil communication was altered by fertilizing plant leaves without changing soil conditions. In this way, we were able to determine the role of plant C:N stoichiometry in the priming effect of the rhizosphere and detritusphere.
Effect of soil C:N:P stoichiometry on plant-microbe-soil interactions
Effect of soil C:N:P stoichiometry on plant-microbe-soil interactions
Keywords: rhizosphere; primming effect; detritusphere; root exudates; DOC